Dampak Kinerja Keuangan Terhadap Return Saham dengan Inflasi sebagai Variabel Moderasi Pada Sektor Industri Barang Konsumsi Kategori Syariah di Bursa Efek Indonesia - Retno Gita Ayuningrum; Muhamad Umar Mai; Rani Putri Kusuma Dewi (Journal of Applied Islamic Economics and Finance, 2021)
Investors can actively make an assessment by analyzing the financial performance of a company. Therefore, this study aims to examine the influence of the company's financial performance factors seen from financial ratios, including the Current Ratio (CR), Debt to Asset Ratio (DAR), Return on Assets (ROA) and Price Earning Ratio (PER) and macroeconomic factors, namely inflation as a moderating variable on stock returns of companies in the consumer goods industry sector in the sharia category listed on the Indonesian Sharia Stock Index (ISSI). A sample of 25 companies that meet the research criteria with purposive sampling method. The data analysis technique used is descriptive analysis and path analysis. With the help of software WrapPLS version 7.0. The results showed that ROA and PER had a positive and significant effect on stock returns. While CR and DAR have no effect on stock returns. And inflation cannot moderate the effect of financial performance on stock returns.